ANALISIS USER EXPERIENCE DAN REDESIGN FITUR FANTASY TEAM PADA APLIKASI VIDIO DENGAN METODE DESIGN THINKING MELALUI PENDEKATAN USER EXPERIENCE QUESTIONNAIRE - Rifqi Aria Bramantyo, (2023)
The development of information technology in the era of the 4.0 technological revolution is progressing rapidly. Especially during the COVID-19 pandemic. Many mobile applications have experienced an increase in usage during the pandemic. This is due to the increased needs of the community during the pandemic, such as healthcare and entertainment. Vidio is one of the entertainment applications that operates in the field of video streaming services and has been positively affected. Vidio continues to innovate to retain users and enhance user engagement with the Vidio application. One of the innovations is the gamification feature called Fantasy Team. In a questionnaire conducted with 102 individuals, 82% stated that a redesign of the Fantasy Team feature in the Vidio application was necessary. To ensure whether the interface is aligned with user needs and identify the issues experienced by users, the researcher conducted an analysis using the User Experience Questionnaire (UEQ) method. It was found that the Fantasy Team feature of the system received negative evaluation results. The researcher then carried out a redesign using the Design Thinking method. The results obtained from testing the redesigned Fantasy Team feature received positive evaluations and aligned with user needs.